2020
DOI: 10.2147/jpr.s226616
|View full text |Cite
|
Sign up to set email alerts
|

<p>Combining Transcranial Direct Current Stimulation and Transcutaneous Electrical Nerve Stimulation to Relieve Persistent Pain in a Patient Suffering from Complex Regional Pain Syndrome: A Case Report</p>

Abstract: Purpose: Complex regional pain syndrome (CRPS) is a rare neuropathic pain condition characterized by sensory, motor and autonomic alterations. Previous investigations have shown that transcranial direct current stimulation (tDCS) and transcutaneous electrical nerve stimulation (TENS) can alleviate pain in various populations, and that a combination of these treatments could provide greater hypoalgesic effects. In the present case report, we describe the effect of tDCS and TENS treatment on pain intensity and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 49 publications
1
15
1
3
Order By: Relevance
“…Pain decrease in parallel with an increase in the worst finger PIP active ROM resembles the changes reported after 15-30 sessions of transcutaneous electrical neurostimulation (TENS) (71)(72)(73)(74) or after 5 sessions of TENS in combination with brain stimulation (75). Thus, the similarity with our results after only one session of rPMS suggest that rPMS in CRPS was likely more efficient than TENS in CRPS.…”
Section: Pain and Functionsupporting
confidence: 87%
“…Pain decrease in parallel with an increase in the worst finger PIP active ROM resembles the changes reported after 15-30 sessions of transcutaneous electrical neurostimulation (TENS) (71)(72)(73)(74) or after 5 sessions of TENS in combination with brain stimulation (75). Thus, the similarity with our results after only one session of rPMS suggest that rPMS in CRPS was likely more efficient than TENS in CRPS.…”
Section: Pain and Functionsupporting
confidence: 87%
“…As also outlined in Table 1, a total of six articles and 125 NP patients were involved in tDCS treatment. Among them, five studies Studies of rTMS treatment are labeled yellow, studies of tDCS treatment are labeled green, and studies of ineffective treatment are labeled gray rTMS repetitive transcranial magnetic stimulation, tDCS transcranial direct current stimulation, ACC anterior cingulate cortex, PSI posterior superior insula, M1 primary motor cortex, DLPFC dorsolateral prefrontal cortex, PMC premotor cortex, S1 primary somatosensory cortex, S2 secondary somatosensory cortex involving 95 NP patients (76.0%) also showed that tDCS successfully relieved NP [39,40,43,44]. Thirty NP patients (24.0%) did not experience pain relief, as reported by Jensen MP et al [41].…”
Section: Categories Of Np In the Present Reviewmentioning
confidence: 99%
“…Other conditions, such as complex regional pain syndrome (CRPS) [44], fibromyalgia, or polyneuropathy [41], can also cause NP. Among NIBS-treated patients with TNP induced by other sources (n = 14) (Fig.…”
Section: Other Snpsmentioning
confidence: 99%
“…Similarly, less favorable efficacy of primary motor rTMS has been observed in lower limb neuropathic pain relative to face or upper limb neuropathic pain for (42,43). It should be noted that Houde et al (15) did not include a TENS only condition and that the time interval between tDCS and TENS may have been too short to differentiate the analgesic effect of tDCS alone from the potential synergetic effect of both interventions. Furthermore, tDCS was not used as a biomarker in the setting of patient selection for chronic epidural MCS.…”
Section: Discussionmentioning
confidence: 99%